Conductivity, dielectric and modulus study of chitosan-methyl cellulose - BMIMTFSI polymer electrolyte doped with cellulose nano crystal - Misenan M.S.M.; Ali E.S.; Azwani Sofia Ahmad Khiar (American Institute of Physics Inc., 2024)
Indexed by WOS/ Scopus